2021
DOI: 10.1101/2021.07.04.21259992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Late surges in COVID-19 cases and varying transmission potential partially due to public health policy changes in 5 Western states, March 10, 2020-January 10, 2021

Abstract: Objective: This study investigates how the SARS-CoV-2 transmission potential varied in North Dakota, South Dakota, Montana, Wyoming, and Idaho from March 2020 through January 2021. Methods: Time-varying reproduction numbers, Rt, of a 7-day-sliding-window and of non-overlapping-windows between policy changes were estimated utilizing the instantaneous reproduction number method. Linear regression was performed to evaluate if per-capita cumulative case-count varied across counties with different population size.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…School reopening has been reported by several studies to increase transmission of SARS-CoV-2. [39] , [40] , [41] In our study, the Policy Change R t increase after school reopening was statistically significant in Iberia and East Baton Rouge parishes, Louisiana (75 th and 100 th percentile population size) and Hinds, Mississippi (100 th percentile size). A mathematical modeling study on school reopening reported that it was associated with increased risk in urban regions.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…School reopening has been reported by several studies to increase transmission of SARS-CoV-2. [39] , [40] , [41] In our study, the Policy Change R t increase after school reopening was statistically significant in Iberia and East Baton Rouge parishes, Louisiana (75 th and 100 th percentile population size) and Hinds, Mississippi (100 th percentile size). A mathematical modeling study on school reopening reported that it was associated with increased risk in urban regions.…”
Section: Discussionmentioning
confidence: 45%
“…Meanwhile, rural-urban disparities was generally not observed in the Appalachian region of Kentucky and both Delta and non-Delta regions of Arkansas over much of 2020. [33] In a study of 5 Western states, [41] North Dakota was the only state where densely populated counties consistently had a higher per-capita cumulative incidence throughout 2020. Rural counties in Louisiana and Mississippi continued to experience a higher burden in the first half of 2021.…”
Section: Discussionmentioning
confidence: 99%
“…39 Hua et al found that a mask mandate was associated with a decrease in R t by 27% in North Dakota, by 16% in Montana and by 13% in Wyoming. 40 Politis et al found facemask mandate was associated with a decrease in R t by 11% and 6%, respectively, in Arkansas and Kentucky. 10 Thus, our findings in South Carolina are consistent with findings in other states that a mask mandate was associated with slowing epidemic growth.…”
Section: Discussionmentioning
confidence: 98%
“…39 Hua et al found that a mask mandate was associated with a decrease in Rt by 27% in North Dakota, by 16% in Montana and by 13% in Wyoming. 40 Politis et al found facemask mandate was associated with a decrease in Rt by 11% and 6%, respectively, in Arkansas and Kentucky. 10 Thus, our findings in South Carolina are consistent with findings in other states that a mask mandate was associated with slowing epidemic growth.…”
Section: Discussionmentioning
confidence: 98%
“…37,[42][43][44] Similar to our findings, Hua et al found an increase in Rt in Idaho (13%), Montana (21%), South Dakota (12%) and Wyoming (20%) after school reopened on September 7, 2020; however, the same study found a decrease in Rt by 8% in North Dakota after school re-opening on the same date. 40 Politis et al found that after school reopened, Rt increased by 12% and 9% in Arkansas and Kentucky, respectively. 10 Thus, our findings in South Carolina are consistent with findings in other states in general, that school re-opening in August and September 2020 was associated with increased SARS-CoV-2 transmission as evidenced in an increase in Rt.…”
Section: Discussionmentioning
confidence: 99%